2018
DOI: 10.1101/440750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing reliability of intra-tumor heterogeneity estimates from single sample whole exome sequencing data

Abstract: Tumors are made of evolving and heterogeneous populations of cells which arise from successive appearance and expansion of subclonal populations, following acquisition of mutations conferring them a selective advantage. Those subclonal populations can be sensitive or resistant to different treatments, and provide information about tumor aetiology and future evolution. Hence, it is important to be able to assess the level of heterogeneity of tumors with high reliability for clinical applications.In the past few… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…In recent years, a large number of methods have been developed to unravel ITH in tumors [7, 18, 8, 22, 6], and have been applied to different cohorts, including the TCGA. Recent analyses illustrate limits encountered when applying those methods to bulk WES [23, 10], as the number of observed mutations is small, the variance in read counts can be high, and a unique sample may miss the heterogeneity of the tumor. As sequencing costs are continuously decreasing, WGS, multi-sample sequencing and single cell sequencing will constitute relevant alternatives and simplify the study of ITH.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a large number of methods have been developed to unravel ITH in tumors [7, 18, 8, 22, 6], and have been applied to different cohorts, including the TCGA. Recent analyses illustrate limits encountered when applying those methods to bulk WES [23, 10], as the number of observed mutations is small, the variance in read counts can be high, and a unique sample may miss the heterogeneity of the tumor. As sequencing costs are continuously decreasing, WGS, multi-sample sequencing and single cell sequencing will constitute relevant alternatives and simplify the study of ITH.…”
Section: Discussionmentioning
confidence: 99%
“…Both WGS and WES have limited sensitivity for studying intra-tumor heterogeneity in single samples 73,74 . Bulk sequencing of multiple tumor regions still misses many subclones, particularly when subclones are not evenly distributed across the tumor mass.…”
Section: Evolution Of the Fieldmentioning
confidence: 99%
“…Indeed, recent results showed that the MATH score is heavily affected by the choice of mutation-calling algorithm, and its robustness and prognostic significance have been questioned [102]. Another study [103] compared the accuracy and robustness of six clonality inference methods on WES TCGA data and found that the resulting estimates were highly confounded by tumor purity or mutational load. Similar observations have been made for tumor phylogenetic reconstruction and mutation ordering methods [104].…”
Section: Immune Heterogeneitymentioning
confidence: 99%